Radiation Oncologist Consultations Prior to Radical Prostatectomy: Disparities and Opportunities. Issue 1 (27th January 2022) - Corkum, Mark T.; Loblaw, D. Andrew; Morton, Gerard; ,; Louie, Alexander V.; ,; Glicksman, Rachel; ,; Chin, Joseph; ,; Kulkarni, Girish; ,; et al.
Abstract : Purpose: In 2015, men undergoing radical prostatectomy in Ontario, Canada were recommended to undergo multidisciplinary care by seeing a radiation oncologist or discussion at multidisciplinary rounds before surgery. The a priori target rate was ≥76%. We used population-based data to explore factors associated with not receiving multidisciplinary care prior to radical prostatectomy. Materials and Methods: Men who underwent radical prostatectomy for localized prostate cancer in Ontario between 2007 and 2017 were identified using administrative data. Physician billings identified patients who received multidisciplinary care. Multivariable logistic regression was used to predict receipt of multidisciplinary care. Results: A total of 31, 485 men underwent radical prostatectomy between 2007 and 2017. Of these patients 28.7% saw a radiation oncologist, 1.2% underwent multidisciplinary discussion and 1.9% had both before surgery. Multidisciplinary care receipt increased from 17.8% in 2007 to 47.8% in 2017 (p <0.001). The odds ratio between the highest and lowest geographic regions was 7.93 (95% CI 6.17–10.18, p <0.001). Lower odds of multidisciplinary care receipt were observed for men further from the nearest cancer center (OR 0.74 per 50 km, 95% CI 0.71–0.78, p <0.001) and higher odds for the highest versus lowest income quintile (OR 1.41, 95% CI 1.29–1.54, p <0.001). Of 128 urologists who performed ≥10 radical prostatectomies between 2016 and 2017, 29 (22.7%) met the target of having ≥76% of men seen for multidisciplinary care prior to surgery. Conclusions: Despite increasing utilization, many men do not receive multidisciplinary care prior to radical prostatectomy. While geography and the urologist appear to be the greatest factors predicting multidisciplinary care receipt, these factors are closely intertwined.